Europe in the Balkan Mirror - Milutinović, Zoran (Balcanica - Annual of the Institute for Balkan Studies, 2015)
The article discusses the three dominant, Europe-wide, constructions of Europe in the nineteenth and twentieth centuries, and claims that all three found their proponents in the Balkans in the same period, while no specifically Balkan construction of Europe can be identified. The discourses which constructed Europe were transnational, and every search for national discourses must recognize that they are always fractured and contradictory, composed of various elements originating in Europe-wide discourses on Europe. Throughout this period the dominant discourse of Europe was shaped by the discourse of modernity and modernization, not only in Europe but in other parts of the globe as well. Several commentators have already noted that the current challenge of the interwar construction of Europe – peace, prosperity, democracy and human rights – mirrors the crisis of Yugoslavia, and many examples point to the unsustainability of this construction at the beginning of the twenty-first century. Gadamer’s hermeneutics offers a valuable lesson in humility and defines the oft-repeated phrase of “belonging together” as listening to the other in the belief that the other may be right, which should be taken as a starting point for any future construction of Europe.